Studies of plant density increase – on maize hybrids of various genotypes on chernozem soil - Murányi, Eszter; Pepó, Péter (Acta Agraria Debreceniensis, 2014)
The yield and crop safety of maize are influenced by numerous ecological, biological and agrotechnical factors. It is of special importance to study one of the agrotechnical elements, the plant density of maize hybrids, which is influenced by the growing area conditions and the selected hybrid.We have investigated the effects of three different plant numbers (50 thousand plants ha-1, 70 thousand plants ha-1 and 90 thousand plants ha-1) on the yield of 12 maize hybrids of different genotypes in Hajdúság, on calcareous chernozem soil, in the Látókép Research Farm of the University of Debrecen, Centre for Agricultural Sciences, in 2013. The experiment was set in four replications, besides commonly applied agrotechnical actions. In the experiment, 1 hybrid of very early (Sarolta), 9 of early (P 9578, DKC 4014, DKC 4025, P 9175, NK Lucius, Reseda, P 37N01, DKC 4490, P 9494) and 2 of medium (Kenéz, SY Afinity) maturation were used.With the increase of the plant number, the number of individuals per unit area increases. According to our experimental results, we have concluded that with the increase of the plant number, the yield increased in the average of the hybrids. In the average of the hybrids, in the case of 50 thousand plants ha-1, the yield was 13 130 kg ha-1, in the case of 70 thousand plants ha-1, it was 13 824 kg ha-1, while in the case of 90 thousand plants ha-1, the yield became 13 877 kg ha-1.In addition to plant density increase, it is necessary to determine the optimal plant number that is the most favourable for the certain hybrid under the given conditions. To fulfil this aim, we have determined the optimal plant number corresponding to the maximum yield of the given hybrid, within the given plant number range. The optimal and applied plant numbers differ, since the optimal one could only be applied under ideal conditions. Since the agrotechnical actions cannot always be carried out in appropriate quality and one has to adapt to the weather conditions, thus we have determined a plant number range in the case of each hybrid. The hybrids were classified into categories of producible in narrow and broad plant number range.